Aplicação de processos oxidativos avançados e biológicos para o tratamento de efluente da produção de antibióticos - Rafaela Brito Portela Marcelino (2014)
Antibiotics have gained increasing distinction in the academic community because they are considered emerging and dangerous pollutants. A growing concern about the risk of potential ecotoxic effects and spread of bacterial resistance has encouraged researches to study the application of advanced oxidation processes for the degradation of this type of drug. However, most of the works presented in the literature studies the degradation of synthetic antibiotic solutions and few papers study the degradation of these compounds in real wastewaters. In this context, this study aims to inquiry the application of advanced oxidation processes as well as their combination with biological processes for the treatment of a real wastewater from the production of antibiotics of a pharmaceutical industry. The real wastewater studied has high organic matter content and high levels of antibiotic compounds. Aerobic and anaerobic biodegradability assays indicated that, despite considered biodegradable, wastewaters were proved to be highly toxic after acute ecotoxicity tests. Advanced oxidation processes assessed (Fenton, photo-Fenton/UV, ozonation and ozonation assisted with hydrogen peroxide) were able to remove some of the organic matter present in the wastewater, reaching up to 69 % of COD removal by the photo- Fenton process and up to 99% of amoxicillin removal by the ozonation process. The evaluated AOP could also remove unwanted parameters such as color and aromatics content. Acute toxicity tested with Aliivibrio fischeri bacteria decreased after the treatments, but it is still considered high. In preliminary studies involving Fenton process, coagulation with iron III was evaluated and proved to be important for the removal of antibiotics present in the wastewater. Also, the formation of complexes between iron and amoxicillin was observed. The exploratory evaluation of the combination of advanced oxidation processes with biological processes and/or physical- chemical processes, such as coagulation, for example, proved to be able to decrease operational costs in more than 50% , in addition to raising COD removals up to 98.5% and, thereby, enabling the implementation of the studied processes in industrial scale.